The level of systemic thinking skills (perceiving relationships and structure) in mathematics among female primary school students in Al-Makhwah Governorate - Al-Bogami, Mona Sultan Musleh; Al-Maliki, AbdulMalik Misfer; Al-Maliki, Sultan Safar (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the level of systemic thinking skills in mathematics among elementary school female students, focusing on two specific skills: perception of systemic relationships and system construction. To achieve the study objectives, the researchers adopted the descriptive survey method based on the study’s goals and questions. The sample consisted of 80 students randomly selected from one of the province’s schools. The study instrument was a test designed by the researchers to measure systemic thinking skills for sixth-grade students, with validity and reliability confirmed. Percentages, means, and standard deviations were used to analyze the results. The study revealed that the level of systemic thinking skills (perception of systemic relationships and system construction) in mathematics among sixth-grade students was low, with mastery levels ranging between 48% and 51%, which is below the set mastery benchmark of 60%. The study recommended several actions, including equipping mathematics teachers with modern teaching strategies to enhance students’ systemic thinking skills and focusing on professional development programs for elementary school mathematics teachers to better teach systemic thinking skills.